Improving the mental health of working women with work-life conflict: A protocol development for an explanatory mixed method study - Zahra Hosseini; Seyyede Fateme Rahimi; Fatemeh Salmani; Mohammad Reza Miri; Teamur Aghamolaee; Reza Dastjerdi (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Today, one problem facing working women is the conflict between work and life, and the resultant stress has a great impact on their mental health. A well-known model for stress management is Lazarus and Folkman's model. The primary goal of the present study is to improve working women's mental health through stress management. MATERIALS AND METHODS: The present study employs a mixed approach and is conducted in 4 phases. The target population is women working in Birjand University (South Khorasan province/Eastern Iran). The first step is to describe the research population of a cross-sectional study. The measurement instrument used is Carlson's standard work-life conflict measurement questionnaire. The sample size in this step is 319. The second step is to conduct a qualitative study by interviewing working women with work and life conflict. The sampling will continue until data saturation and then the data will be analyzed through a content analysis. The third step will be the development of a questionnaire based on Lazarus and Folkman's model using the information obtained from the qualitative step. This questionnaire will be then validated in the target research population. Moreover, an exploratory factor analysis, a confirmatory factor analysis and a reliability test will be run. The last step is to carry out an educational intervention to measure the effect of the intervention on stress management and general health in working women with work and life conflict. The measurement instruments used in this step are Cohen's Perceived Stress Questionnaire, General Health Questionnaire, and a researcher-made stress management questionnaire. CONCLUSION: It seems that the educational intervention of stress management with educational content designed based on the needs of the audience, can be effective in controlling and managing the stress caused by women's work-life conflict. TRIAL REGISTRATION: IRCT (IRCT20210918052508N1) from the Iranian Registry of Clinical Trials in 2021-09-21.